Divergence and convergence: Paul Samuelson on economic development - Mauro Boianovsky (Duke University, Center for the History of Political Economy (CHOPE), 2019)
The theory of economic development was an exception to Paul Samuelson's claim of being a "generalist" in economics. It was a hard subject to tackle analytically because of the intrinsic difficulty of some of the concepts involved, such as increasing returns and long-term economic evolution. Nevertheless, Samuelson was aware of the utmost practical relevance of the topic, and discussed at length, sometimes critically, the empirics of development and the theories and policies put forward by development economists, particularly in connection with market failures that could help to explain underdevelopment phenomena. Moreover, he paid more attention than most development economists to the Malthusian demographic dimension of poverty. On the other hand, development planners made use of Samuelson's turnpike theorems of growth theory, and reacted, mostly critically, to his factor price equalization (FPE) theorem of international trade and its apparent conflict with income divergence between developed and underdeveloped economies.
Keywords: 330; Samuelson; economic development; divergence; convergence; increasing returns